2011
DOI: 10.1002/jbm.a.33138
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated neovascularization and endothelialization of vascular grafts promoted by covalently bound laminin type 1

Abstract: Development of a small diameter (<6 mm) synthetic vascular graft with clinically acceptable patency must overcome the inherent thrombogenicity of polymers and the development of neointimal thickening. Establishment of an endothelial cell lining on the lumenal surface has been hypothesized as a mechanism to improve the function of vascular grafts. The major aim of this study was to evaluate the use of laminin type 1, covalently bound to all surfaces of ePTFE grafts on neovascularization of the interstices and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 39 publications
0
46
0
Order By: Relevance
“…For example, mimicking the fibrillar ECM structure in the form of micron-sized gratings on synthetic surfaces has been shown to increase migration and retention under shear stress [15], improve proliferation [16] and retain the atheroprotective phenotype [17] of endothelial cells. Additionally, functionalization of synthetic surfaces with ECM proteins, such as fibronectin [18], vitronectin [19] and laminin [20] were shown to improve endothelial cell attachment. Anucleate platelets are also sensitive to both biochemical and biophysical cues [21,22], showing changes in morphology and activation.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mimicking the fibrillar ECM structure in the form of micron-sized gratings on synthetic surfaces has been shown to increase migration and retention under shear stress [15], improve proliferation [16] and retain the atheroprotective phenotype [17] of endothelial cells. Additionally, functionalization of synthetic surfaces with ECM proteins, such as fibronectin [18], vitronectin [19] and laminin [20] were shown to improve endothelial cell attachment. Anucleate platelets are also sensitive to both biochemical and biophysical cues [21,22], showing changes in morphology and activation.…”
Section: Introductionmentioning
confidence: 99%
“…[69][70][71][72] Laminin type 1 has been utilized in ePTFE grafts, demonstrating enhanced endothelialization over unmodified grafts. 73 While laminin-derived RGD continues to be one of the more popular ECM-derived peptides to enhance endothelialization, 74 a variety of other peptide sequences derived from fibronectin, laminin, and collagen type I have been incorporated into vascular grafts.…”
mentioning
confidence: 99%
“…The presence of red cells, leukocytes, fibrin, and platelets in the control grafts suggested a highly thrombogenic surface, while the laminin type 1 conjugated grafts exhibited a complete lining of cells, indicative of an intact endothelium as shown in Figure 2. The authors also observed neovascularization in the interstices of the ePTFE grafts in the laminin-conjugated grafts (Williams et al, 2011).…”
Section: Bioactive Vascular Prosthesesmentioning
confidence: 86%